Penerapan Supervisi Klinik Model Group dalam Pendokumentasian Asuhan Keperawatan di RSUD Indrasari Rengat - Deswita Deswita; Yulastri Arif; Supiyah Supiyah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Documentation of nursing care is one indicator of the quality of nursing services at the hospital. Documentation of nursing care at Indrasari Rengat Hospital 40% still does not meet the standards, both in completeness standards, implementation standards and relevance standards. The low achievement in documenting nursing care is due to the supervision factor, where supervision is carried out at Indrasari Rengat Regional Hospital is still not optimal, there is no feedback from the head of the room for documentation of nursing care. In this study, researchers applied group model clinical supervision at Indrasari Rengat Regional Hospital, with the aim of seeing the effectiveness of clinical model group supervision of nursing care documentation. This research was carried out from 20 January to 10 August 2015, with a quasi-experimental design, One-Group pretest-Posttest Design. The sample of this study was in the form of 35 patient documents in the inpatient room with simple random sampling technique. The results found a significant difference between documenting nursing care before and after the implementation of clinical model group supervision with p value